APPLYING KWL TECHNIQUE TO INCREASE STUDENTS’ READING COMPREHENSION AT GRADE NINE OF SMP N 30 PEKANBARU - E. Ruth Veronica Gultom; Erni Erni; Rumiri Aruan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is aimed at improving students’reading comprehension and identifying the factors that influence changing of students’s reading comprehension with applying KWL technique at grade nine of SMP N 30 Pekanbaru. Using random cluster sampling, 30 students employed in this study were taken as the sample of this research. This study employed mixed method, combining quantitative and qualitative methods of data collection. The quantitative data were collected from a questionnaire while the qualitative ones were obtained through observation, interview, and field note. The questionnaire consists of five reading indicators; factual information, main idea, supporting idea, reference, and guessing the meaning). The findings of this study revealed that the improvement of students’ reading comprehension in every indicator. This result showed that the improvement of students’ reading comprehension happened because using KWL chart, giving reward to students, and familiar text. The strengths of using KWL technique are; most students were interested, active, and worked independently in doing exercise and test by using KWL technique. In addition, some students also confused in arranging the question and students who could not find their answer within the given time would be disappointed.Key Words: Reading Comprehension, KWL Technique, Students’ Improvement, Pekanbaru